PENGARUH GREEN INVESTMENT, DAN CARBON CREDIT TERHADAP SUSTAINABLE FIRM PERFOMANCE PADA BANK UMUM SYARIAH YANG TERDAFTAR DI BEI - Ningsih, Tiara Setia; Yamin, Mohamad (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study was conducted to determine the Influence of Green Investment and Carbon Credit on Sustainable Firm Performance in Islamic General Banks Listed on the IDX. This study uses Purposive Sampling and uses 14 Islamic General Banks for the 2021-2024 period as research samples. The method used in this study is a quantitative method with data analysis using non-parametric regression tests, determination coefficient tests (R2), F tests, and multicollinearity tests processed using the SPSS program. The results of the study show that the non-parametric regression analysis of the Green Investment and Carbon Credit variables has a positive and significant effect on the three indicators of the Sustainable Firm Performance variable, namely ROA, Total Tree Planting, and Employee Turnover. The Green Investment variable has a significance value of 0.004 (ROA), 0.003 (Total Tree Planting), and 0.047 (Employee Turnover). Meanwhile, the Carbon Credit variable has a significance value of 0.003 (ROA), 0.003 (Total Tree Planting), and 0.011 (Employee Turnover). This finding also shows that green investment efforts and involvement in the carbon credit mechanism are able to support profitability, environmental sustainability, and also social aspects in Islamic Commercial Banks listed on the Indonesia Stock Exchange